The importance and role of negotiations on Iran’s nuclear program (International relations and international law Journal, 2016)
In this article it is analyzed Almaty negotiations on the nuclear program of Iran. Also it is considered as now to nuclear branch of Iran the close attention is shown from the world community and IAEA concern on creation by Iran of capacities on uranium enrichment. In article also it is noted that concerning this country a number of resolutions of the UNSC urging it to stop implementation of programs, the capacities connected with creation on uranium enrichment which can be used for creation of the nuclear weapon is accepted. It is described some positions of the states to negotiations between “six” and Iran. Iran, in turn, defiantly ignores requirements of UNSC and continues course realization on creation of large-scale production objects on uranium enrichment and other capacities of a nuclear fuel cycle for their use as the Iranian party claims, is exclusive in the peace purposes.
Keywords: Iran; the IAEA; the nuclear program of uranium enrichment; nuclear power; the representatives of the “six talks”; the new sanctions; nuclear fuel; national security